Analisis pengaruh gaya komunikasi kepala sekolah dan kompensasi terhadap kinerja guru tidak tetap (GTT) di SD Negeri Jekulo - Annisa Setiyana (IKIP Siliwangi, 2023)
This research is motivated by the gap that occurs between civil servant teachers and non-civil servant teachers in the field. Communication by school principals to GTT teachers is sometimes different from PNS teachers. The same goes for the wages you receive. The importance of providing the right compensation will motivate GTT to continue working professionally and give their best performance. And accompanied by smooth communication between GTT and school principals and PNS teachers, it will have a very good impact on improving the quality of education in schools. Based on this, the formulation of the problem in this study is